Development of the Concept of Freedom among Children and Adolescences in Kurdistan Region of Iraq - Mohammed, Zahid S.; Al-zebari, Sabir A.S.; Alajeely, Shaza A.M. (Humanities Journal of University of Zakho, 2018)
The aim of the current study was to measure the development of concept of freedom among children and adolescences in Kurdistan Region of Iraq among ages (12,16,20) with variables of gender and occupation of parents of participants of the study. The sample of the study (1461) consisted of students from schools of basic, secondary and university education in Zakho. The sample of the study was chosen intended randomly. The researcher prepared a scale consisting of (48) oral situations with variables of (Yes, I am not sure and No). After applying validity, reliability and pilot study of the study, the average was found (0.84). T-test and Anova of statistical package for social sciences (SPSS) were used to find out the results of the study. The following statements are the results of the study: There was statistical difference in developmental of concept of freedom among variables of stages of ages (12, 16, 20), with the level of development of concept of freedom increasing with age. There was significant difference among the participants of the study and the level of developmental of concept of freedom was higher among females. There was no statistically significant difference in developmental of concept of freedom among the variable of occupation of parents. According to the results of the study the researcher gave several recommendations and suggestions.